PENGARUH FLEXIBLE WORK ARRANGEMENT DAN BEBAN KERJA TERHADAP KEPUASAN KERJA DENGAN WORK-LIFE BALANCE SEBAGAI VARIABEL MEDIASI PADA RECRUITER GENERASI MILENIAL PERUSAHAAN START-UP DI JAKARTA SELATAN - Namira Dinda Hermawan (2023)
This study that aims to explain the effect of flexible work arrangements and workload on job satisfaction with work-life balance as its mediating variabel on milennial generation employees of startup companies in Jakarta Selatan. This study uses a quantitative approach. The sample of this study, is 96 of milennial recruiter of startup companies in Jakarta Selatan. To analyze the data, this study uses Likert scale method and uses analytichal methods and SmartPLS software to process the data. The results of this study are (1) flexible work arrangements doesn't have impact and not significant on job satisfaction, (2) workload has a positive and significant impact on job satisfaction, (3) work-life balance can mediate between flexible work arrangement and job satisfaction and has positive impact on both, (4) work-life balance can mediate between workload and job satisfaction and has positive and significant impact on both, and (5) work-life balance has positive and significant impact on job satisfaction.